Click Chemistry in Natural Product Modification - Zhang, Xiang; Zhang, Shuning; Zhao, Songfeng; Wang, Xuan; Liu, Bo; Xu, Hongtao (Frontiers in Chemistry, 2021)
Click chemistry is perhaps the most powerful synthetic toolbox that can efficiently access to the molecular diversity and unique functions of complex natural products up to now. It enables the readily synthesis of diverse sets of natural product derivatives either for the optimization of their drawbacks or for the construction of natural product-like drug screening libraries. This paper showcases the state-of-the-art development of click chemistry in natural product modification, summarizes the pharmacological activities of the active derivatives as well as the mechanism of action. The aim of this paper is to gain a deep understanding of the fruitful achievements and to provide perspectives, trends and directions regarding further research in natural product medicinal chemistry.